A bio-guided assessment of the anti-inflammatory activity of hop extracts (Humulus lupulus L. cv. Cascade) in human gastric epithelial cells. (June 2019) - Sangiovanni, Enrico; Fumagalli, Marco; Santagostini, Laura; Forino, Martino; Piazza, Stefano; Colombo, Elisa; Taglialatela-Scafati, Orazio; Fico, Gelsomina; Dell'Agli, Mario
Graphical abstract: Highlights: The hydroalcoholic extract from hop cones inhibits IL-8 release and NF-κB pathway. In vitro gastric digestion of hop extract slightly alters biological activity. Chalcones may act as major contributors to the anti-inflammatory activity. First demonstration of the anti-inflammatory activity of xanthohumol D in AGS cells. Abstract: The present work aims to characterize and investigate the anti-inflammatory activity of hop extracts (cv. Cascade) in an in vitro model of gastric inflammation. The biological activities of hydroalcoholic and aqueous extracts from cones were evaluated by comparing IL-8 inhibition induced by TNFα. The hydroalcoholic extract demonstrated a higher inhibitory effect, which was just slightly affected by an in vitro simulated gastric digestion. The identification of active compounds was performed by a bio-guided fractionation which afforded 11 fractions, one of which inhibited IL-8 release in a concentration-dependent fashion in human gastric epithelial AGS cells. Phytochemical analysis revealed xanthohumol A and xanthohumol D as the main active components. The present study provides some experimental evidences that Humulus lupulus L. may exert an anti-inflammatory activity on the gastric district by the inhibition of the IL-8 secretion, partially due to its prenylated chalcones content.